Parent Involvement in Increased Children's Application - sa'diya, Lida khalimatus; Wahyuningrum, Tria; Purwati, Heni (Kirana Publisher (KNPub), 2022)
The nutritional status of toddlers is an important thing that every parent must know and the need for more attention to growth and development at the age of toddlers is based on the fact that malnutrition that occurs in toddlers is irreversible (cannot be recovered) Marimba, 2010. According to Andi Nurlinda, 2012 Nutritional status is one indicator in determining the health status of children. Good nutritional status can help the growth and development of children to reach optimal maturity. Touch and massage therapy for babies has many benefits for the baby's physiological changes, especially if the baby's mother does it herself. Mother is the closest parent to the baby, and the massage of the mother to her baby is a gentle stroke of binding the fabric of affection. The mother's skin is the skin that the baby recognizes first (Aminati, 2013). Massage is one of the complementary therapies that many parents choose. According to Roesli (2013), touch therapy (massage) can have a positive physical effect, including weight gain. Tui Na massage is a more specific massage technique to overcome eating difficulties in toddlers by improving blood circulation in the spleen and digestion (Sukanta, 2010). This research is a literature review design. The data used is secondary data obtained from the results of research that has been carried out by previous researchers whose research journals have been published that are relevant to the topic, starting from 2015 to 2021 which are accessed in full text. Yuni's research results, 2019 that there is an effect of tui na massage on weight gain. The results of the study by Titik, 2017 that Tui Na Massage is effective in increasing the weight of toddlers. The results of Happy's research, 2019 that there is an effect of massage on increasing the appetite of toddlers aged 1 year. There is an effect of massage on the increase in appetite for toddlers aged 1 year. Based on the results of the research above, the child's appetite and weight after being given tui na massage treatment, the average growth of weight gain increased and appetite increased above the average baby who did not get massage treatment.